2018
DOI: 10.22462/07.08.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Injection of SVF combined with HBO2 improves viability of unfavorably designed flaps

Abstract: Purpose: Soft-tissue reconstruction is complicated by ischemia and reperfusion injury. Animal trials have documented the independent healing benefits of hyperbaric oxygen preconditioning (HBOP) and stem cell delivery in cutaneous flaps. We explored the role of HBOP and stem cell delivery in flap preconditioning and survival. Methods: We designed a randomized controlled trial to assess the effects of hyperbaric oxygen preconditioning and stromal vascular fraction (SVF) delivery on flap survival. Of the first 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The anti-apoptotic nature of SVF has however not been as extensively studied as its potential to differentiate into other cell types, although it does seem promising. For example, recently, Lee et al [ 17 ] described how SVF injections significantly decreased apoptosis and TUNEL labeling in a rat model of acute kidney injury, and Tenenhaus et al [ 18 ] showed how necrosis after soft tissue reconstruction can be minimized using SVF injections.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-apoptotic nature of SVF has however not been as extensively studied as its potential to differentiate into other cell types, although it does seem promising. For example, recently, Lee et al [ 17 ] described how SVF injections significantly decreased apoptosis and TUNEL labeling in a rat model of acute kidney injury, and Tenenhaus et al [ 18 ] showed how necrosis after soft tissue reconstruction can be minimized using SVF injections.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of drugs and physical methods are used in the study of random flap necrosis. Because of the complexity of the flap necrosis mechanism, many scholars have adopted combined therapy for prevention and treatment and achieved good results 31,32 . Photobiomodulation, as a noninvasive method, has been widely used clinically and has been shown to reduce necrosis in the ischemic flap, which is an ideal adjuvant treatment for other treatments 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complexity of the flap necrosis mechanism, many scholars have adopted combined therapy for prevention and treatment and achieved good results. 31,32 Photobiomodulation, as a noninvasive method, has been widely used clinically and has been shown to reduce necrosis in the ischemic flap, which is an ideal adjuvant treatment for other treatments. 26 In the present study, we found that red-blue light improved flap survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBO-PC improved myeloid, B cell, and T-cell engraftment in a murine transplant model (Aljitawi et al 2014 ). The combination of HBO-PC and stem cell therapy has been successfully used in cutaneous flaps (Tenenhaus et al 2018 ) and traumatic brain injury(Zhou et al 2016 ).…”
Section: Potential Mechanism Of Hbo-pc For Ismentioning
confidence: 99%